Agronomic biofortification and productivity of wheat with soil zinc and diazotrophic bacteria in tropical savannah - Jalal, Arshad [UNESP]; Oliveira, Carlos Eduardo Da Silva [UNESP]; Freitas, Leandro Alves [UNESP]; Galindo, Fernando Shintate; Lima, Bruno Horschut [UNESP]; Boleta, Eduardo Henrique Marcandalli [UNESP]; Da Silva, Edson Cabral; Nascimento, Vagner Do [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Buzetti, Salatiér [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (CSIRO Publishing, 2022)
Agronomic biofortification of staple food with zinc (Zn) in combination with diazotrophic bacteria is one sustainable and feasible strategy to improve plant nutrition, nutrient use efficiency and production and combat Zn malnutrition in human beings. Wheat (Triticum aestivum L.) is a staple food of the global population and has a prospective role in agronomic Zn biofortification. In this context, the effect of diazotrophic bacterial inoculations in seeds (no inoculation - Control, Azospirillum brasilense, Bacillus subtilis and Pseudomonas fluorescens) in association with soil Zn application (without (0) and 8 kg/ha) was evaluated on Zn nutrition, growth, yield and Zn use efficiencies in wheat in the 2019 and 2020 cropping seasons. Soil Zn application in combination with P. fluorescens improved Zn concentration in the leaf (38.8 and 45.9%), shoot (25.0 and 31%) and grain (34.0 and 33.3%) with greater shoot dry matter (9.4 and 9.9%) and grain yield (20.3 and 20.6%) as compared to controls in 2019 and 2020 respectively. Also, inoculation of P. fluorescens with Zn application improved Zn shoot and grain accumulation, zinc use efficiency, recovery and utilisation efficiency. With daily wheat consumption, these improvements would be associated with a with higher estimated Zn intake for the human population globally and within Brazil. However, agro-physiological efficiency was increased with inoculation of Bacillus subtilis. Therefore, inoculation of P. fluorescens in association with soil Zn application is recommended for agronomic biofortification, and to increase productivity and Zn use efficiencies in wheat in the tropical savannah of Brazil.
Keywords: Bacillus subtilis; bacteria inoculation; Pseudomonas fluorescens; Triticum aestivum L; zinc fertilisation; Zn accumulation; Zn biofortification; Zn use efficiency